RapidSplint: virtual splint generation for orthognathic surgery – results of a pilot series. (January 2014) - Adolphs, Nicolai; Liu, Weichen; Keeve, Erwin; Hoffmeister, Bodo
Abstract Background: Within the domain of craniomaxillofacial surgery, orthognathic surgery is a special field dedicated to the correction of dentofacial anomalies resulting from skeletal malocclusion. Generally, in such cases, an interdisciplinary orthodontic and surgical treatment approach is required. After initial orthodontic alignment of the dental arches, skeletal discrepancies of the jaws can be corrected by distinct surgical strategies and procedures in order to achieve correct occlusal relations, as well as facial balance and harmony within individualized treatment concepts. To transfer the preoperative surgical planning and reposition the mobilized dental arches with optimal occlusal relations, surgical splints are typically used. For this purpose, different strategies have been described which use one or more splints. Traditionally, these splints are manufactured by a dental technician based on patient-specific dental casts; however, computer-assisted technologies have gained increasing importance with respect to preoperative planning and its subsequent surgical transfer. Methods: In a pilot study of 10 patients undergoing orthognathic corrections by a one-splint strategy, two final occlusal splints were produced for each patient and compared with respect to their clinical usability. One splint was manufactured in the traditional way by a dental technician according to the preoperative surgical planning. After performing a CBCT scan of the patient's dental casts, a second splint was designed virtually by an engineer and surgeon working together, according to the desired final occlusion. For this purpose, RapidSplint®, a custom-made software platform, was used. After post-processing and conversion of the datasets into .stl files, the splints were fabricated by the PolyJet procedure using photo polymerization. During surgery, both splints were inserted after mobilization of the dental arches then compared with respect to their clinical usability according to the occlusal fitting. Results: Using the workflow described above, virtual splints could be designed and manufactured for all patients in this pilot study. Eight of 10 virtual splints could be used clinically to achieve and maintain final occlusion after orthognathic surgery. In two cases virtual splints were not usable due to insufficient occlusal fitting, and even two of the traditional splints were not clinically usable. In five patients where both types of splints were available, their occlusal fitting was assessed as being equivalent, and in one case the virtual splint showed even better occlusal fitting than the traditional splint. In one case where no traditional splint was available, the virtual splint proved to be helpful in achieving the final occlusion. Conclusions: In this pilot study it was demonstrated that clinically usable splints for orthognathic surgery can be produced by computer-assisted technology. Virtual splint design was realized by RapidSplint®, an in-house software platform which might contribute in future to shorten preoperative workflows for the production of orthognathic surgical splints.